PBL-Based Student Worksheet to Improve Critical Thinking Ability in Science Learning in Elementary Schools - Pramudiyanti, Pramudiyanti; Pratiwi, Wulan Octi; Armansyah, Armansyah; Rohman, Fatkhur; Putri, Intan Yulia; Ariani, Devi (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study aims to create a student worksheet based on the Problem-based Learning (PBL) model in science learning, test its feasibility, and identify student and teacher responses to the implementation of the student worksheet. The instruments were validation sheets and student and teacher response questionnaires. The research data were descriptively and qualitatively analyzed based on the criteria score. Material expert validation obtained an average of 0.8409 with